Michael Roemer American Trilogy - Roemer, Michael 1928-; Roemer, Michael 1928-; Rath, Franz 1932-2020; Adams, Brooke 1949-; DeVries, Jon; Matson, Audrey (Camelia, 2024)
Unsuccessfully trying to close old family wounds on a trip back to the Rhode Island home of her miserable childhood, a troubled Brooke Adams finds her new friendship with neighbor Trish Van Devere has her stuck in another family drama. [imdb.de]
Bildformat: 1,66:1
Orig.: USA, 1984
Keywords: Film; Blu-Ray-Disc